Pengaruh Price Perception, Location, dan Product Quality Terhadap Repurchase Intention pada Konsumen Dapur Juice Jumbo Jombang - Munawaroh, Ismi; Dwijayani, Henny; Aslichah, Aslichah (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
The competition in the juice beverage business in Jombang Regency is becoming increasingly tight, so Dapur Juice Jumbo Jombang needs to retain consumers to encourage repeat purchases. This study aims to analyze the influence of price perception, location, and product quality on the repurchase intention of Dapur Juice Jumbo Jombang consumers, both partially and simultaneously, as well as to identify the most dominant variable. The method used is quantitative, involving 80 respondents selected through a questionnaire. The sampling technique employs non-probability sampling with an accidental sampling method. Data analysis techniques use multiple linear regression with SPSS 25. The results show that the location variable does not have a significant effect on repurchase intention, while price perception and product quality have a significant effect, with price perception being the most dominant variable. Simultaneously, all three variables influence repurchase intention.Based on these results, Dapur Juice Jumbo Jombang needs to maintain prices that are in line with product quality and continue to improve product quality so that consumers are willing to make repeat purchases.